Uji Efektivitas Nefroprotektif Ekstrak Buah Kersen (Muntingia calabura L) Terhadap Kadar Kreatinin Pada Tikus Putih Yang Diinduksi Gentamicin - Femy Cecilia Marbun; Asyrun Alkhairi Lubis; Edy Fachrial (Journal of Pharmaceutical and Sciences, 2026)
Introduction: Gentamicin, an aminoglycoside antibiotic, is widely used for severe Gram-negative bacterial infections but poses a significant risk of nephrotoxicity, characterized by elevated serum creatinine levels. Muntingia calabura L. (cherry fruit) contains bioactive compounds with potential nephroprotective properties. Objective: This study aimed to evaluate the nephroprotective effect of cherry fruit extract on serum creatinine levels in gentamicin-induced white rats. Methods: An experimental post-test only control group design was employed using 25 male Wistar rats divided into five groups: normal control (K1), gentamicin control (K2), and treatment groups receiving gentamicin plus cherry fruit extract at doses of 100 (K3), 200 (K4), and 400 (K5) mg/kgBW. Gentamicin (100 mg/kgBW/day) was administered intraperitoneally for 7 days, while the extract was given orally for the same period. Serum creatinine levels were measured using the Jaffe method and analyzed using One-way ANOVA. Results: Serum creatinine levels in the gentamicin control group were 0.64 ± 0.09 mg/dL, while treatment groups K3, K4, and K5 showed levels of 0.62 ± 0.09, 0.61 ± 0.06, and 0.59 ± 0.10 mg/dL, respectively. Statistical analysis revealed no significant differences among groups (p > 0.05). A dose-dependent decreasing trend was observed, with the 400 mg/kgBW dose showing the lowest creatinine level, approaching the normal control value (0.55 ± 0.05 mg/dL). Conclusion: Cherry fruit extract demonstrated a tendency toward nephroprotective effects, indicated by dose-dependent reduction in serum creatinine levels; however, the effect was not statistically significant. Further research incorporating additional parameters, including BUN, renal histopathology, and oxidative stress biomarkers, is necessary to confirm its nephroprotective potential.